Peranan Mata Kuliah Pengembangan Kepribadian Bagi Lulusan Perguruan Tinggi yang Berkarakter - Beni Habibi (Universitas Pancasakti Tegal, 2018)
The purpose of this study is to describe how the process and role of character education at Pancasakti University Tegal. Data obtained by observation and in-depth interview to a number of lecturers, employees, students of character education players in a limited lane at the University of Pancasakti Tegal. These data sources are not randomly selected, but are determined on people who are considered to know a lot about the issues under study. Data processing runs simultaneously with data collection, as well as through triangulation process to obtain the provision of data that has been tested. The results of the study provide an illustration that the implementation of character education at Pancasakti Tegal University runs through various units, namely the Personality Development Unit, the Student Activity Unit and the Kerokhanian unit. Each has been running well, but the three units need to be synergized and continuously improved. The implication of this research is that the group of character education improvement at Pancasakti University must be comprehensively upgraded and continuously improved so that the result can really be useful.